2007
DOI: 10.1111/j.1471-0528.2007.01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gestational hypercholesterolaemia on omental vasoreactivity, placental enzyme activity and transplacental passage of normal and oxidised fatty acids

Abstract: Objective Maternal hypercholesterolaemia during pregnancy increases lipid peroxidation in mothers and fetuses and programs increased susceptibility to atherosclerosis later in life. The objective of this study was to elucidate the role of the placenta in mediating oxidative stress from mother to offspring.Design Comparison between normo-and hypercholesterolaemic mothers (n = 36 each) and their children.Setting Obstetric wards, hospitals of the University of Naples and Regione Campania.Population Healthy primip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 50 publications
0
48
0
2
Order By: Relevance
“…Maternal oxidative stress in a high cholesterol environment may adversely affect the placenta and may directly or indirectly enhance atherosclerotic lesions in the offspring (44). Experiments in hypercholesterolemic rabbits have shown that administration of the antioxidant vitamin E during pregnancy resulted in reduced atherosclerotic lesions in the offspring (16,17), indicating that maternal oxidative stress likely plays a role in maternal programming for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal oxidative stress in a high cholesterol environment may adversely affect the placenta and may directly or indirectly enhance atherosclerotic lesions in the offspring (44). Experiments in hypercholesterolemic rabbits have shown that administration of the antioxidant vitamin E during pregnancy resulted in reduced atherosclerotic lesions in the offspring (16,17), indicating that maternal oxidative stress likely plays a role in maternal programming for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…This cut-off point is similar to TCh level in pregnant women showing increased oxidative stress in maternal and fetal blood, and homogenized placenta, and exhibit reduced maternal omental artery reactivity and altered composition of the fetal blood fatty acids. 31 Furthermore, increased early atherosclerosis markers, such as fatty streaks and lipid peroxidation, in human fetal aorta 5 or in 7-to 14-year-old children 32 born from mothers with TCh level over this cut-off point is reported. Because TCh, HDL-C, and triglyceride plasma by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from levels were unaltered in newborns from women with MSPH, confirming previous observations, 33,34 we speculate on the possibility that MSPH is a pathological condition of the mother coursing with altered human fetoplacental vasculature.…”
Section: Msph Cut-off Pointmentioning
confidence: 94%
“…In fact, studies in humans have shown that the placenta is both the target of maternal oxidative stress and a modulator of fetal oxidative stress. 15 Furthermore, extensive data exist on atherogenic programming of arterial endothelial cells by maternal hypercholesterolemia, obesity, the metabolic syndrome, and diabetes. 16,17 It is therefore likely that changes in HPEC signaling are similarly early and extensive.…”
mentioning
confidence: 99%